Artificial Intelligence-Enhanced Instructional Media Design: Phenomenological Insights from Pre-Service Islamic Education Teachers - Umar; Suhendi; Ghulam Murtadlo; Purwiro Harjati; Makmur Harun (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study explores how pre-service Islamic Education teachers experience and interpret the use of Artificial Intelligence (AI) in designing instructional media during a teaching practicum program. Moving beyond performance-based evaluations of AI integration, the study conceptualizes AI as a socio-technical system that mediates pedagogical reasoning and professional identity formation. Using a qualitative phenomenological approach, data were collected through in-depth interviews, classroom observations, and document analysis involving eight undergraduate students. The data were analyzed using Interpretative Phenomenological Analysis (IPA) to uncover the lived meanings of AI use in instructional practice. The findings reveal four interconnected themes: AI as a transformational tool in media creation, AI as a pedagogical support, AI as a catalyst for reshaping classroom dynamics, and AI as a mediating presence in the becoming of novice teacher identity. Participants experienced a transition from perceived limitation to expanded capability, accompanied by increased confidence and reflexivity. At the same time, AI integration generated ethical and pedagogical tensions requiring critical judgment and contextual sensitivity. These findings suggest that AI in teacher education functions not merely as a technical enhancer, but as an identity-mediating presence that reshapes authority, engagement, and professional self-understanding within value-laden educational contexts. The study contributes theoretically by extending AI-in-education discourse toward phenomenological inquiry and value-sensitive technology integration.